How Do Socio-Cultural and Built Environment Characteristics Influence Urban Vitality and Walkability in Bahrain’s Commercial Streets? Insights from Muharraq - Mohamed, Afaf Ebrahim; Allani, Najla (Alanya Üniversitesi, 2025)
Shopping streets serve as vital socio-economic and cultural hubs, fostering urban vitality and enhancing liveability. In Bahrain, however, limited attention has been paid to how socio-cultural dynamics and built environment characteristics shape walkability within commercial avenues. This study investigates these interrelationships through a case study of Shaikh Hamad Avenue in Muharraq, one of Bahrain’s oldest shopping streets. Employing a qualitative research design, data were collected via 135 structured questionnaires, systematic on-site observations, and GIS-based mapping of pedestrian movement patterns. The findings reveal that walkability perceptions are significantly influenced by five determinants: imageability, enclosure, human scale, complexity, and safety. Elements such as shade provision, shop diversity, and spatial connectivity were found to encourage pedestrian activity, whereas inadequate crossings and climatic constraints hinder walkability. Results highlight the importance of integrating culturally sensitive design, pedestrian-oriented infrastructure, and micro-scale amenities into planning strategies. The study contributes evidence-based insights for policymakers and urban designers to enhance commercial street environments, promoting inclusive, dynamic, and sustainable urban spaces in Bahrain and similar Gulf contexts.